2020
DOI: 10.1101/2020.07.29.226761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allosteric inhibition of the SARS-CoV-2 main protease – insights from mass spectrometry-based assays

Abstract: Following translation of the SARS-CoV-2 RNA genome into two viral polypeptides, the main protease Mpro cleaves at eleven sites to release non-structural proteins required for viral replication. MPro is an attractive target for antiviral therapies to combat the coronavirus-2019 disease (COVID-19). Here, we have used native mass spectrometry (MS) to characterize the functional unit of Mpro. Analysis of the monomer-dimer equilibria reveals a dissociation constant of Kd = 0.14 ± 0.03 μM, revealing MPro has a stron… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In another study, El‐baba et al investigated the SARS‐CoV‐2 main protease known to play a role in viral replication. Monomer/dimer equilibrium was analyzed in the presence of several small molecules that non‐covalently bound to the protease slowing down the substrate processing, thereby optimizing the use of antiviral compounds in this context (El‐Baba et al, 2020). Native and denaturing top‐down MS‐based approaches to determine the glycosylation of the SARS‐CoV‐2 S‐protein and its interaction with the ACE2 receptor is described in Section 3.4.…”
Section: Proteomics‐based Ms Of Sars‐cov‐2‐infected Nasopharyngeal Sw...mentioning
confidence: 99%
“…In another study, El‐baba et al investigated the SARS‐CoV‐2 main protease known to play a role in viral replication. Monomer/dimer equilibrium was analyzed in the presence of several small molecules that non‐covalently bound to the protease slowing down the substrate processing, thereby optimizing the use of antiviral compounds in this context (El‐Baba et al, 2020). Native and denaturing top‐down MS‐based approaches to determine the glycosylation of the SARS‐CoV‐2 S‐protein and its interaction with the ACE2 receptor is described in Section 3.4.…”
Section: Proteomics‐based Ms Of Sars‐cov‐2‐infected Nasopharyngeal Sw...mentioning
confidence: 99%
“…2D and 6) and suggesting that nsp7-11 binding stabilizes the Mpro dimer. In this sense, El-Baba and colleagues (61) identified that fragment JGY-discovered through crystallographic fragment screening and binding in the dimer interface (30)-destabilized the Mpro dimer and showed ~35% inhibition of the rate of processing at 100 μM. Along the same lines, Sun and colleagues (62) discovered a nanobody, NB2B4, which binds the C-terminal domain of monomeric Mpro (PDB 7VFB) and inhibits activity with an IC 50 ~150 nM.…”
Section: Discussionmentioning
confidence: 99%
“…Work of Robinson and Vakonakis 192 focused on the protease M encoded by the SARS-COV-2 RNA genome. Its role is to process several of the virus structural proteins.…”
Section: ■ Mass Spectrometry In the Era Of Covid-19mentioning
confidence: 99%